2002
DOI: 10.1098/rspb.2002.2008
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of parasites from their hosts: intra– and interspecific parasitism and Emery's rule

Abstract: In some taxa of Hymenoptera, fungi, red algae and mistletoe, parasites and their hosts are either sibling species or at least closely related (Emery's rule). Three evolutionary mechanisms have been proposed for this phenomenon: (i) intraspeci c parasitism is followed by sympatric speciation; (ii) allopatric speciation is followed by secondary sympatry and the subsequent parasitism of one sibling species by the other; and (iii) allopatric speciation of a species with intraspeci c parasitism is followed by secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 13 publications
2
32
0
2
Order By: Relevance
“…This is typically in accordance with the Emery's rule (Emery, 1909), which proposes speciation patterns to explain how the 60 S. Dronnet et al parasites and their hosts would have evolved jointly (Schmid-Hempel, 1998;Lowe et al, 2002). If Emery's rule was applied for bumblebees, one species of inquiline should be phylogenetically close to its host species.…”
Section: Introductionmentioning
confidence: 80%
“…This is typically in accordance with the Emery's rule (Emery, 1909), which proposes speciation patterns to explain how the 60 S. Dronnet et al parasites and their hosts would have evolved jointly (Schmid-Hempel, 1998;Lowe et al, 2002). If Emery's rule was applied for bumblebees, one species of inquiline should be phylogenetically close to its host species.…”
Section: Introductionmentioning
confidence: 80%
“…Among those who study socially parasitic eusocial Hymenoptera, there has been much discussion concerning whether they follow Emery's Rule, which posits that social parasites and their hosts are closely related (Lowe et al 2002;Huang and Dornhaus 2008). In many ants Emery's Rule does seem to apply, but in other eusocial Hymenoptera, such as vespine wasps, studies have shown that social parasites are not closely related (Carpenter and Perera 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These are normally derived from ancestral host traits (Emery 1909) because social parasites are sister clades (the "loose" version of Emery's rule) or even sister species (the "strict" version of Emery's rule). Emery's rule has been hypothesized to be consistent with sympatric speciation (Elmes 1978;Buschinger 1986), but allopatric explanations for the evolution of social parasitism cannot be excluded (Wilson 1971;Lowe et al 2002). A recently discovered example of the strict version of Emery's rule is the Panamanian leafcutting ant Acromyrmex insinuator, which is an inquiline social parasite of its host and sister species Acromyrmex echinatior (Schultz et al 1998;Sumner et al 2004a).…”
Section: Introductionmentioning
confidence: 99%